2021
DOI: 10.1016/j.jml.2020.104206
|View full text |Cite
|
Sign up to set email alerts
|

Priming reveals similarities and differences between three purported cases of implicature: Some, number and free choice disjunctions

Abstract: Across a wide variety of semantically ambiguous sentences, implicature has been proposed as a single mechanism which can derive one reading from another in a systematic way. While a single formal mechanism for computing implicatures across disparate cases has an appealing parsimony, differences in behavioral and processing signatures between cases have created a debate about whether the same computation really is so widely shared. Building on previous work by Bott & Chemla (2016), three experiments use structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Rees and Bott (2018) found that activating stronger alternative propositions in the minds of comprehenders made them more likely to endorse a scalar implicature. Bott and Frisson (2022) found that presenting stronger alternative propositions decreased response times when comprehenders were computing a scalar implicature (for more recent findings on scalar implicature priming, see Marty et al, 2024;Meyer & Feiman, 2021;Waldon & Degen, 2020) To directly test which alternatives are activated in the minds of comprehenders, recent lexical priming studies have examined scalar expressions. De Carvalho and colleagues (2016) showed that weaker scale-mates activated their strong terms more than the strong did the weak scalars.…”
Section: The Priming Of Scalar Termsmentioning
confidence: 99%
“…Rees and Bott (2018) found that activating stronger alternative propositions in the minds of comprehenders made them more likely to endorse a scalar implicature. Bott and Frisson (2022) found that presenting stronger alternative propositions decreased response times when comprehenders were computing a scalar implicature (for more recent findings on scalar implicature priming, see Marty et al, 2024;Meyer & Feiman, 2021;Waldon & Degen, 2020) To directly test which alternatives are activated in the minds of comprehenders, recent lexical priming studies have examined scalar expressions. De Carvalho and colleagues (2016) showed that weaker scale-mates activated their strong terms more than the strong did the weak scalars.…”
Section: The Priming Of Scalar Termsmentioning
confidence: 99%
“…Implicature or implicit meaning can be identified in an utterance and is therefore a logical consequence of language use (Betti & Khalaf, 2021;Meyer & Feiman, 2021;Qin & van Compernolle, 2021;Sbisà, 2021;Terkourafi et al, 2021). Even implicit meaning has to be used in response to culture.…”
Section: I1 Theoretical Highlightsmentioning
confidence: 99%
“…Priming provides a method of tapping into the underlying structure of language and has been influential in shaping our knowledge of adult and child language (for reviews see Branigan & Pickering, 2018). Bott and Chemla (2016; see also Meyer & Feiman, 2021) demonstrated that in adults, scalar and ad hoc implicatures can be primed so that there is a greater rate of implicatures when an implicature is presented in the preceding trial than when a literal meaning is presented in the preceding trial. Moreover, Rees and Bott showed that implicatures can be primed with the alternative in the same way.…”
Section: Priming Enrichment In Childrenmentioning
confidence: 99%